Financial accounting - Duchac, Jonathan E. (Thomson/South-Western, 2007)
This integrated framework focuses on providing students with a sound understanding of how the financial statements work together to provide a picture of a company's financial performance, while at the same time teaching students the impact of transactions on the financial statements. This methodology offers a blend of concepts and procedures, which helps students get to the "ah-ha" moment in accounting education sooner by focusing on how the financial statements come together BEFORE introducing debits and credits